Protocols for treating patients with end‐stage renal disease: a survey of undergraduate dental programs. (8th August 2016) - Sturgill, Jeremiah; Howell, Scott; Perry, Maureen Munnelly; Kothari, Hemali
ABSTRACT: Rationale/Background: Approximately 14% of Americans are living with chronic kidney disease (CKD). The prevalence of end‐stage renal disease (ESRD), the result of progressing CKD continues to rise by 21, 000 per year. There are no updated, evidence‐based antibiotic prophylaxis guidelines for patients with renal disease undergoing dental treatment. The most recent was a scientific statement from the American Heart Association (AHA) in 2003. Presented in three parts, the goal of the first part of this study is to determine the current protocol being used to treat renal patients at U.S. dental schools. Methods and Materials: A 21 multiple‐choice question survey was e‐mailed to 58 clinic deans of accredited dental schools in the United States regarding renal treatment protocol details including antibiotic prophylaxis. Results: Fifty‐two percent of programs report having no established renal patient treatment protocol. For programs with a protocol, when using prophylactic antibiotics, 54% followed AHA protocol, whereas 62% used a modified protocol. Conclusion: There is a lack of consistent, established protocols among undergraduate dental programs. It is suggested that evidence‐based guidelines for the safe treatment of patients be developed.